2010
DOI: 10.1093/pubmed/fdq052
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage and public reaction to a celebrity cancer diagnosis

Abstract: Increased public interest in disease prevention can follow a celebrity diagnosis. Although media coverage sometimes included public health information, articles typically focused on secondary instead of primary prevention. There is further potential to maximize the public health benefit of future celebrity diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 29 publications
(21 reference statements)
5
66
1
1
Order By: Relevance
“…26,30 However, content analysis of media reports of Jade Goody's experiences demonstrated that less than 5% of newspaper reports mentioned risk factors for cervical cancer, with just 8.2% of articles mentioning screening, but 41% mentioning the terminal nature of her illness and 36% reporting on her treatment. 14,26 Consistent with studies demonstrating a lack of preventive information in media reports of cancer or cancer screening, 31 -34 the comparative lack of mobilizing information regarding screening Table1 Proportion of eligible women aged 20 -64 years, for whom routine cervical screening invites were issued, responding to a screening invitation either before receiving a screening invitation or within the month following receipt between and prevention may have precluded longer-term impacts on behaviour. In contrast to cervical screening uptake, colposcopy referrals continued to increase in the two years following the start of media reporting of Jade Goody, reflecting the sustained impact of the increase in smear tests carried out.…”
Section: Discussionmentioning
confidence: 87%
“…26,30 However, content analysis of media reports of Jade Goody's experiences demonstrated that less than 5% of newspaper reports mentioned risk factors for cervical cancer, with just 8.2% of articles mentioning screening, but 41% mentioning the terminal nature of her illness and 36% reporting on her treatment. 14,26 Consistent with studies demonstrating a lack of preventive information in media reports of cancer or cancer screening, 31 -34 the comparative lack of mobilizing information regarding screening Table1 Proportion of eligible women aged 20 -64 years, for whom routine cervical screening invites were issued, responding to a screening invitation either before receiving a screening invitation or within the month following receipt between and prevention may have precluded longer-term impacts on behaviour. In contrast to cervical screening uptake, colposcopy referrals continued to increase in the two years following the start of media reporting of Jade Goody, reflecting the sustained impact of the increase in smear tests carried out.…”
Section: Discussionmentioning
confidence: 87%
“…Even though this could affect the sensitivity of our results, this repetitive behavior may indicate the difficulty of these individuals in solving their dental problems, perhaps due to the lack of adequate counseling or the influence of health barriers, such as the unavailability of specialized dental services and unfavorable financial conditions. Fourth, overestimations might be produced for individuals without dental caries who search for the condition as a result of other stimuli, such as media reports, health campaigns, and personal attitudes [Metcalfe et al, 2010]. Fifth, the automatic algorithms provided by Google Trends are kept in secret, as a "black box" [DeRouen, 2015].…”
Section: Brazilmentioning
confidence: 99%
“…[10][11][12][13] With news being commonly sourced from online outlets that promote reader participation through posted comments, strategies that support a proactive, real-time public health response would be useful. A communications strategy is needed that provides clear, accurate and accessible information, counters negative attitudes to smokers and supports smokers to make quit attempts, but also engages with online news readers.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies of the impact of celebrity health stories have reported improvements in health behaviours such as cancer screening and information seeking. 10,11 However, any important, factual health information reported in these newsworthy 'human interest' storylines tends to be overshadowed by the celebrity-focused content, suggesting missed opportunities for public health practitioners to use these stories as a communication opportunity. 9,12,13 Studies of online news reporting and reader responses are increasingly relevant.…”
Section: Introductionmentioning
confidence: 99%